Analisis Faktor Faktor Yang Memengaruhi Penjualan Online pada mahasiswa STIE Mandala Jember - Tamriatin Hidayah; Hary Sulaksono (RELASI : JURNAL EKONOMI, 2021)
This study aims to look at the effect of Price, Ease, Information Quality, Safety and Confidence variables on Online buying decisions. Data collection method using purposive sampling, with 100 respondents. Data analysis method using Multiple Linear Regression Analysis with independent variables namely price, convenience, quality of information, security and trust. The dependent variable used is an online purchasing decision. This study uses quantitative data with primary data sources. Primary data in question, obtained from the object of research directly by distributing questionnaires to 100 respondents. The results showed that the price, convenience, quality of information, security and trust variables had a significant positive effect on online purchasing decisions both partially and simultaneously on the students of STIE Mandala Jember. The conclusion of this study was that price, ease, convenience, quality of information, security and trust influence online buying decisions. Keywords: Price, Ease, Quality of information, Security, Trust, Buying Decision